The effect of sugammadex on steroid hormones: A randomized clinical study - Gut, Gulay Gunduz; Ozer, Ayse B.; Demirel, Ismail; Aksu, Ahmet; Erhan, Omer L. (Elsevier Science Inc, 2016)
Study objective: Sugammadex is an alternative drug to traditional decurarization by cholinesterase inhibitors. It has been examined the effect of sugammadex on steroid hormones in this study. Design: Randomized clinical trial. Setting: The study was conducted in a University Teaching Hospital from January 2013 to May 2014. Patients: Fifty male patients between 18 and 45 years of age with an American Society of Anesthesiology (ASA) class I or II undergoing elective lower extremity surgery were included in this study. Interventions: Patients were categorized into two groups (neostigmin group, Group N; and sugammadex group, Group S). In addition to standard monitorization, train-of-four (TOF) was also used to monitorize the level of neuromuscular blockade. Standard induction and maintenance of anesthesia were performed. At the termination of surgery, neuromuscular blockade was antagonized using 0.05 mg/kg of neostigmine and 0.01 mg/kg of atropin when spontaneous recovery of neuromuscular blockade occurred with the reappearance of T2 in Group N and using 4 mg/kg sugammadex in Group S. Measurements: The primary outcome in this study was to determine serum aldosterone, cortisol, progesterone, and free testosterone levels. Three blood samples were obtained in each patient just before and 15 minutes and 4 hours after antagonism, Main results: No significant differences were found in demographic characteristics between the groups. While there were no differences in serum progesterone levels, patients in neostigmin group had significantly higher cortisol levels at 15 minutes as compared to baseline. Also, patients in sugammadex group had significantly higher serum aldosterone and testosterone levels 15 minutes after antagonism as compared to those in the neostigmine group. Conclusions: Our findings suggest that sugammadex is not associated with adverse effects on steroid hormones progesterone and cortisol, while it may lead to a temporary increase in aldosterone and testosterone. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Sugammadex; cortisol; insulin; progesterone; aldosterone